Identifying the necessary requirements for a safe cardiac surgery checklist (Research, Society and Development, 2021)
Objective: To identify the necessary requirements for a safe cardiac surgery checklist. Methodology: This is descriptive research of a mixed nature using data collection and interviews. The setting for data collection was a large general hospital located in northeastern Brazil that performs cardiac surgery. The interviews took place by using a semi-structured questionnaire applied to nurses who worked in the surgery room. The project was approved by the Research Ethics Committee under number CAAE 16286219.8.0000.5013 and opinion 3.606.131. Results: Five interviews were conducted. All interviewees considered important the use of a specific checklist for cardiac surgery due to the safety of the patient, professionals and the contribution to the management and specificity of cardiac surgery. The checklist evaluated in the hospital had all the elements arranged in the instrument for direct observation; therefore, being specific for cardiac surgery. Conclusion: Based on the research results, the perception of nursing professionals about the importance of using the checklist is favorable, because even if the main objective is patient safety, the checklist is also useful to manage in a safer way the surgical process and generate data to build hospital indicators. The checklist does not only cover the time of surgery, but the entire surgical process, as it allows the surgery to take place as planned and safely for the patient.